BDS/GNSS for Earth Observation - Jin, Shuanggen; Dardanelli, Gino (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint of the Special Issue "BDS/GNSS for Earth Observation" highlights and discusses major aspects of Earth monitoring. Among the most noteworthy works are articles presenting variations in the plasmaspheric total electron content (TEC) and correlations between the seismo-ionospheric anomalies of GNSS-TEC and earthquake energy. Those addressing the analysis of the Earth's ionosphere employ two new methods developed for determining the optimal thin layer ionospheric height in the polar regions and for estimating the multi-GNSS differential code bias without using the ionospheric function model. In addition, the troposphere is investigated using a modified interpolation method of multi-reference station tropospheric delay. There are two papers addressing precise orbit determination, employing the Haiyang-2b altimetry satellite and GRACE-FO antenna phase center modeling. Works on GNSS signals are also published, with variations in multi-channel differential code biases from new BDS-3 signal observations, and the modelling and assessment of a new triple-frequency IF1213 PPP with BDS/GPS. Furthermore, GNSS precipitable water vapor (PWV) and its applications are discussed with regard to individual station meteorological data, while three other works examine improvements in iGNSS-R ocean altimetric precision, maritime multiple moving target detection using multiple-BDS radar, and a regional groundwater storage anomaly by combining GNSSs and surface mass load data. Lastly, a review addressing the application of multi-GNSS for Earth observation and its emerging applications is presented.